2020
DOI: 10.15294/rainbow.v9i2.39987
|View full text |Cite
|
Sign up to set email alerts
|

Function of The Language Style Used in Women Commercial Product Advertisements: A Stylistic Analysis of Language

Abstract: The objectives of this research are to find out the types of the language style used in selected Woman Commercial Product Advertisement and to explain the function of language style in selected Woman Commercial Product Advertisement. The concept of stylistic is analyzed by using William Wells’s theory which discussed about language style. A qualitative research method is used in analyzing this research. The result of this research shows that some types of language style are found in the data. From 10 advertise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The research findings reveal that in more detail, there are several similarities with research conducted by (Putra and Rosa, 2019), where the dominant language style is relaxed. It is in line with other research conducted by (Ginting, 2020) and (Muthia, 2021), who have different terms, consultative style and casual style, and he uses these terms to have a communication style that can be used for relationships with another context. The researchers found that the most dominant language style often used in the context of communication relationships is the casual style.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The research findings reveal that in more detail, there are several similarities with research conducted by (Putra and Rosa, 2019), where the dominant language style is relaxed. It is in line with other research conducted by (Ginting, 2020) and (Muthia, 2021), who have different terms, consultative style and casual style, and he uses these terms to have a communication style that can be used for relationships with another context. The researchers found that the most dominant language style often used in the context of communication relationships is the casual style.…”
Section: Discussionsupporting
confidence: 87%
“…From the results of his research, he found data on four speech styles, frozen, casual, consultative, and intimate, used by the presenter, Ellen DeGeneres. The third article was taken by (Ginting, 2020) in their research discussing ways to find out the types and functions of the language style used in an advertisement for women's commercial products. In the fourth article by Juliana (Dewi, 2020) in this research, the writer explains how to understand and use language style in discourse analysis.…”
Section: Introductionmentioning
confidence: 99%
“…and Losi and Rosida (2022) analyzed promoting objects in persuasive language. Meanwhile, Ginting et al (2020) and Saputri et al (2021) provide an example of an analysis of advertisements through stylistic analysis. The persuasive language and stylistic analysis results depend on the specific field.…”
Section: Introductionmentioning
confidence: 99%
“…It is purposed to know the language style usage in written advertisement influence the readers to buy and use the beauty products. Furthermore, the study proposed by Ginting et al, (2020), stated that the meaning of utterances interpreted by the hearer following the use of style forms during the interaction. Their study focused on the type of language style and its function in women's commercial product advertisements.…”
Section: Introductionmentioning
confidence: 99%